Online Concentration of Bacteria from Tens of Microliter Sample Volumes in Roughened Fused Silica Capillary with Subsequent Analysis by Capillary Electrophoresis and Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry - Horká, Marie; Šalplachta, Jiří; Karásek, Pavel; Ru Žička, Filip; Roth, Michal (ACS infectious diseases, 2020)
This study presents a timely, reliable, and sensitive method for identification of pathogenic bacteria in clinical samples based on a combination of capillary electrophoresis with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. In this respect, a part of a single-piece fused silica capillary was etched with supercritical water with the aim of using it for static or dynamic cell-surface adhesion from tens of microliter sample volumes. The conditions for this procedure were optimized. Adhered cells of Staphylococcus aureus (methicillin-susceptible or methicillin-resistant) and of Pseudomonas aeruginosa were desorbed and preconcentrated from the rough part of the capillary surface using transient isotachophoretic stacking from a high conductivity model matrix. The charged cells were swep and separated again in micellar electrokinetic chromatography using a nonionogenic surfactant. Static adhesion of the cells onto the roughened part of the capillary is certainly volumetric limited. Dynamic adhesion allows the concentration of bacteria from 100 μL volumes of physiological saline solution, bovine serum, or human blood with the limits of detection at 1.8 × 102, 1.7 × 103, and 1.0 × 103 cells mL-1, respectively. The limits of detection were the same for all three examined bacterial strains. The recovery of the method was about 83% and it was independent of the sample matrix. A combination of capillary electrophoresis with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry required at least 4 × 103 cells mL-1 to obtain reliable results. The calibration plots were linear (R2 = 0.99) and the relative standard deviations of the peak area were at most 2.2%. The adhered bacteria, either individual or in a mixture, were online analyzed by micellar electrokinetic chromatography and then collected from the capillary and off-line analyzed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry without interfering matrix components.
Keywords: Staphylococcus aureus; micely; roughened capillary; Electrophoresis, Capillary; Silicon Dioxide; Bacteriological Techniques; Micelles; Bacterial Adhesion; Pseudomonas aeruginosa; elektroforéza kapilární; cell-surface adhesion; bakteriální adheze; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Hydrogen-Ion Concentration; oxid křemičitý; matrix-assisted laser desorption/ionization time-of-flight mass spectrometry; Bacteria; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; koncentrace vodíkových iontů; capillary electrophoresis; bakteriologické techniky